Dermatological reactions to ophthalmic preparations: More than meets the eye. (13th February 2014) - Byrom, Lisa; Zappala, Tania; Muir, Jim
Abstract Ophthalmic preparations are commonly used medications that have been implicated in causing a variety of dermatological reactions. These reactions include toxic epidermal necrolysis, anaphylaxis, fixed drug eruption, lichenoid drug reaction and local and systemic contact dermatitis. This article reviews the dermatological and systemic reactions associated with ophthalmic preparation use and highlights the need for a thorough medication history to be done for all patients presenting with a suspected drug reaction.